Hedonic Test of Instant Powdered Ginger Drink with Sugar and Sugar-Palm Sugar Combination - Jannah, Husnul; Badi’ah, Baiq Arriyadul; Amalia Rachman, Irna Ningsi; Desimal, Iwan (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Stress, environmental pollution, radiation, and excessive food processing contribute to the production of free radicals, which are harmful to the body. Antioxidants play a role in preventing free radicals from damaging nucleotides. Ginger contains high levels of antioxidants, making it beneficial for overall health. However, ginger has a short shelf life, and its traditional preparation methods are less preferred by many people. Therefore, ginger is now available in the form of instant drink powders, which can be prepared like tea or coffee. This study is a descriptive study using the hedonic test method. Thirty students were selected as panelists. The panelists evaluated two types of ginger drinks made with different sweeteners: sugar and a combination of sugar and palm sugar (sugar-palm sugar). The parameters assessed in this study were color, aroma, taste, and sweetness level. The results of the hedonic test showed that the ginger drink sweetened with the sugar-palm sugar combination had the highest preference percentages across all parameters: color, aroma, taste, and sweetness level. For color, the "like" preference level achieved a percentage of 40%. For aroma, the "really like" preference level reached 43.33%. Taste received a "really like" preference level of 53.33%, and sweetness achieved a "like" preference level of 36.67%. In conclusion, the panelists preferred the ginger drink sweetened with the sugar-palm sugar combination over the drink sweetened with just sugar. This preference is attributed to the addition of palm sugar, which balances the ginger’s strong flavor while retaining its distinct taste. Furthermore, the combination of ginger and palm sugar produces a harmonious blend of color, aroma, taste, and sweetness that complements both ingredients.